PERAN AKSES KESEHATAN DALAM MEMEDIASI VARIABEL PENDAPATAN, TINGKAT PENDIDIKAN DAN STATUS KETENAGAKERJAAN TERHADAP KESEJAHTERAAN PENDUDUK LANJUT USIA DI KOTA DENPASAR - Dharmayanti, Ni Putu Ayu Putri; Sudibia, Ketut; Dewi, Ni Made Heny Urmila (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The success of development can be seen from several indicators, one of which is the increasing life expectancy of the population. The increase life expectancy has resulted in the increasing number of the elderly population from year to year. Improvement of social welfare for the elderly people can also be achieved in many ways. The maximum improvement and utilization of access to health care is one of them to support all the psychological and physical health of the elderly. This study aimed at analyzing: 1) the influence of income, education level and employment status on the access to health care for the elderly people 2) the influence of income, level of education, employment status, and access to health care for the welfare of the elderly 3) the influence of income, education level and employment status on the welfare of the elderly people in Denpasar through access to health care for the elderly.
Keywords: the Elderly Welfare, Health Care Access, Income, Education level, Employment status